To solve the linear-quadratic system using the substitution method, we have the following equations:
- \( y = x^2 - x - 40 \)
- \( y = -3x - 5 \)
We can substitute the expression for \( y \) from the linear equation into the quadratic equation.
So we set \( -3x - 5 \) equal to \( x^2 - x - 40 \):
\[ -3x - 5 = x^2 - x - 40 \]
Now, let's rearrange the equation to form a standard polynomial equation:
\[ 0 = x^2 - x - 40 + 3x + 5 \] \[ 0 = x^2 + 2x - 35 \]
Next, we need to factor the quadratic \( x^2 + 2x - 35 \). We look for two numbers that multiply to \(-35\) and add to \(2\). These numbers are \(7\) and \(-5\).
Thus, we can factor the equation as follows:
\[ (x + 7)(x - 5) = 0 \]
Setting each factor to zero gives us the potential \(x\) values:
- \( x + 7 = 0 \) implies \( x = -7 \)
- \( x - 5 = 0 \) implies \( x = 5 \)
Now, we will find the corresponding \(y\) values for each \(x\):
-
For \( x = -7 \): \[ y = -3(-7) - 5 = 21 - 5 = 16 \] So, one solution is \( (-7, 16) \).
-
For \( x = 5 \): \[ y = -3(5) - 5 = -15 - 5 = -20 \] So, another solution is \( (5, -20) \).
Now we have the two solutions:
- \( (-7, 16) \)
- \( (5, -20) \)
Among your options, the closest representations are:
- \( (5, -10) \) and \( (-7, 26) \) — which are incorrect based on our calculations.
- \( (5, -20) \) and \( (-7, 16) \) — which is the accurate representation of the solutions found.
Therefore, the correct answer is:
(5, -20) and (-7, 16)